Pakistan and the Changing Regional Scenario : Reflections of a Journalist - Mushahid Hussain (Lahore, Pakistan Progressive Publication, 1988)
On Pakistan's geopolitical situation, 1977-1987; includes 93 p. of interviews with foreign dignitaries.
Include Index
Keywords: World politics -- Pakistan